Educating the net generation : a toolkit of resources for educators in Australian universities. - Bennett, Sue; Bishop, Andrea; Chang, Rosemary; Dalgarno, Barney; Gray, Kathleen; Judd, Terry; Kennedy, Gregor; Krause, Kerri-Lee; Maton, Karl; Waycott, Jenny (Australian Learning and Teaching Council, 2009)
This toolkit is one of the outcomes of the ALTC-funded project Educating the Net Generation: Implications for Learning and Teaching in Australian Universities. The resources in this toolkit were developed and used during the project, and include research instruments used to investigate student and staff experiences of technology, and tools used for planning and implementing new technology-based activities in eight learning settings across three universities. The resources in this toolkit can be used by educators to assist in incorporating emerging technologies in educational activities to enhance student learning in discipline-specific contexts. The resources can also be used to support quantitative and qualitative research into the technology experiences and preferences of university students and staff, and the evaluation of technology-based learning activities.